Micro-optical characterization study of highly p-type doped SiC : Al wafers - Wellmann, Peter; Müller, Ralf; Pons, Michel; Thuaire, A.; Crisci, A.; Mermoux, M.; Auvray, L. (Materials Science Forum, 2005)
We have studied the application of optical techniques for the determination of the spatial distribution of electronic properties of highly aluminum doped p-type SiC wafers. Absorption and birefringence mapping are known to be sensitive characterization methods to determine the homogeneity of charge carrier concentration and defects in n-type SiC. In the case of highly p-type doped SiC these methods fail due to the opaque character of the material. In this paper we show that Raman spectroscopy which is a reflective method can be used in order to address the same materials properties like absorption and birefringence. The study was performed using medium doped p-type SiC:Al where optical transmission and reflection methods can be applied simultaneousl
Keywords: Absorption Mapping; Birefringence; p-Type Doping; Raman Mapping